How to B(e)-1 Important Cell During Leishmania Infection - Firmino-Cruz, Luan; Decote-Ricardo, Debora; Gomes, Daniel Claudio de Oliveira; Morrot, Alexandre; Freire-de-Lima, Celio Geraldo; de Matos Guedes, Herbert Leonel (Frontiers in Cellular and Infection Microbiology, 2020)
B-1 cells are an innate-like population of B lymphocytes that are subdivided into B-1a and B-1b distinguished by the presence or absence of CD5, respectively. B-1 cells can act as regulatory B cells, are able to present antigen and produce IL-10. Leishmaniasis in humans is a complex of diseases caused by parasites of the genus Leishmania. More than 20 species can infect humans, with each species causing the development of different immunological responses in the host. Susceptibility is usually related to the production of anti-inflammatory cytokines while the production of Th1 cytokines is indicative of resistance. However, few studies have attempted to evaluate the role of B-1 cells during either the in vivo infection or in vitro interaction with Leishmania parasites. In vivo studies were performed using XID mice model, BALB/Xid mice have a mutation in the Bruton's tyrosine kinase, which is an important enzyme for developing B-1 and maturing B-2 lymphocytes leading to the presence of immature B-2 cells. Here, we compile these studies and assess the influence of B-1 cells on disease progression with different Leishmania species.